UTJECAJ KONATIVNIH KARAKTERISTIKA NA REZULTATSKU USPJEŠNOST U NEKIM SPORTSKIM IGRAMA KOD UČENICA SREDNJE ŠKOLE - Edin Mirvić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
For the purpose of establishing the conative characteristics to result in some sport games (basketball, volleyball and fieldball), at physical education lesson I'm planning to analyse the results of regression analysis in latent got upon selective sample of 120 examiners at the age of 16- 18 years. In this sample have been collected the facts for estimation of conative and situatinomotoric space. In the space of conative characteristics have been taken 4 variables for estimation of pathological characteristics. As instrument measures for estimation of conative characteristics have been chosen scales: Anxiety, Inhibit conversion, Aggression and Schism. In the space of variables for estimation of results in some sport games (basketball, volleyball and fieldball), have been applied 9 situation-motoric tests, to three test for each sport game. According to this examiners can achieve better results if they are a little bit aggressive, if they have a low level of schism, anxiety and inhibit reactions, as shown the results of regressive analysis in latent space.